Fishing methods in upper Ganga River system of Central Himalaya, India - Singh, Gurnam; Agarwal, Naresh Kumar (Journal of Fisheries, 2014)
Present study on fishing methods in the upper Ganga River system was conducted during the period 2010-2012. Upper Ganga river system consists of two major rivers basins viz. Alaknanda and Bhagirathi rivers and number of their 1st and 2nd order tributaries which flows through Garhwal region (Central Himalaya). This large network of fluvial water resources harbours rich Ichthyofaunal diversity. The varied potential of fish resources from these water bodies permits the utilization of wide array of fishing methods. Most of the fishing methods of the Garhwal region are primitive, based on indigenous traditional knowledge and well suited to turbulent nature of the streams. In present study eighteen fishing methods and gears have been documented from the upper Ganga River system. Study observed season, habitat and species specificity of the fishing methods. The utilization of crude and unscientific fishing methods is frequent in the streams of remote areas resulting into decline in fish resource. All the fishing methods employed in upper Ganga River system are classified into four types. The classification is based on their utilisation up to the level which will allow the sustainable harvesting and proper management of valuable fish resources.